2017
DOI: 10.3389/fmicb.2016.02173
|View full text |Cite
|
Sign up to set email alerts
|

Azole Antifungal Resistance in Candida albicans and Emerging Non-albicans Candida Species

Abstract: Within the limited antifungal armamentarium, the azole antifungals are the most frequent class used to treat Candida infections. Azole antifungals such as fluconazole are often preferred treatment for many Candida infections as they are inexpensive, exhibit limited toxicity, and are available for oral administration. There is, however, extensive documentation of intrinsic and developed resistance to azole antifungals among several Candida species. As the frequency of azole resistant Candida isolates in the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
463
8
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 590 publications
(548 citation statements)
references
References 142 publications
13
463
8
17
Order By: Relevance
“…These results were confirmed by the SEM images of CgS (Figure 10(D,E)) and CgR (Figure 11(D,E)), which showed that fewer cells and cell agglomerates were more sparsely distributed on the substrate. It has been reported that C. glabrata has a decreased intrinsic susceptibility to FLZ and other classes of azole antifungals [42,50,51]. Nevertheless, the results of the present study showed that biofilm formation with 40 µg/mL of FLZ for CgS and 1,280 µg/mL of FLZ for CgR can reduce the cell viability of these microorganisms.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…These results were confirmed by the SEM images of CgS (Figure 10(D,E)) and CgR (Figure 11(D,E)), which showed that fewer cells and cell agglomerates were more sparsely distributed on the substrate. It has been reported that C. glabrata has a decreased intrinsic susceptibility to FLZ and other classes of azole antifungals [42,50,51]. Nevertheless, the results of the present study showed that biofilm formation with 40 µg/mL of FLZ for CgS and 1,280 µg/mL of FLZ for CgR can reduce the cell viability of these microorganisms.…”
Section: Discussioncontrasting
confidence: 75%
“…FLZ is often a chosen treatment for Candida infections because of its low cost and availability for oral administration [42]. This drug prevents the biosynthesis of ergosterol through the cytochrome P450 enzyme 14-α demethylase, which catalyzes the conversion of lanosterol to ergosterol [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The both triazoles similarly as rhodamine 6G are well known substrates for Saccharomyces cerevisiae Pdr5p [18] and Cdr1p which is its homologue in the cells of C. albicans [19]. The observed simultaneously resistance to both tested triazoles and rhodamine 6G allows rather to conclude about resistance phenotype generated by ef lux pumps than by genes associated with the ergosterol synthesis as even ERG3 or ERG11 [17]. An additional proof of the existence of this particular phenotype in the case of our isolate are the results of studies with tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…There are different molecular mechanisms of azole resistance that were reviewed in the literature [17]. The both triazoles similarly as rhodamine 6G are well known substrates for Saccharomyces cerevisiae Pdr5p [18] and Cdr1p which is its homologue in the cells of C. albicans [19].…”
Section: Discussionmentioning
confidence: 99%